2019
DOI: 10.1002/pbc.27949
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal development of cancer‐related fatigue and physical activity in childhood cancer patients

Abstract: Purpose Cancer‐related fatigue is one of the most distressing side effects of childhood cancer treatment. Physical activity can decrease fatigue and has positive effects on other health outcomes. Most research on physical activity pertains to adults, and the few studies that focus on children have limited follow‐up time. This study evaluates cancer‐related fatigue in children and its association with physical activity over a one‐year time period. Methods Sixty‐eight children with cancer (7–18 years) were recru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
52
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(62 citation statements)
references
References 37 publications
1
52
0
5
Order By: Relevance
“…In the recently-published paper on the randomized MUCKI trial (on 33 patients so far, which goes to show how challenging it is to design randomized studies), the authors found a positive effect of exercise on fatigue ( 42 ). We know that fatigue interferes with an individual's ability to engage in everyday life activities and social roles (including educational and work opportunities), and that it causes mood swings, impairs social relations, and lowers academic achievement ( 21 , 22 ). One of the strengths of our study lies in that we examined several dimensions of HRQoL and fatigue, and the correlations between physical health, psychological functioning and fatigue as a whole.…”
Section: Lessons Learned and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the recently-published paper on the randomized MUCKI trial (on 33 patients so far, which goes to show how challenging it is to design randomized studies), the authors found a positive effect of exercise on fatigue ( 42 ). We know that fatigue interferes with an individual's ability to engage in everyday life activities and social roles (including educational and work opportunities), and that it causes mood swings, impairs social relations, and lowers academic achievement ( 21 , 22 ). One of the strengths of our study lies in that we examined several dimensions of HRQoL and fatigue, and the correlations between physical health, psychological functioning and fatigue as a whole.…”
Section: Lessons Learned and Discussionmentioning
confidence: 99%
“…Positive associations have been reported between HRQoL and fitness levels in childhood cancer survivors ( 18 , 19 ). Cancer-related fatigue is a common and distressing condition that significantly lowers the HRQoL of patients with cancer ( 20 , 21 ), but higher levels of physical activity have been associated with lower levels of cancer-related fatigue ( 22 ). The literature on the prevalence of cancer-related fatigue in children and adolescents is contradictory ( 23 ).…”
Section: Introductionmentioning
confidence: 99%
“…Physical activity levels were shown to be associated with fatigue levels during a one-year follow-up in a mixed cohort of childhood cancer patients and survivors [ 69 ]. Muscle strength was suggested to be related to fatigue in patients with advanced cancer [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies found that fatigue was the most common adverse effect in adults with CML receiving TKItherapy, and fatigue was also the main reason for the worse HRQoL in adult patients [21,[30][31][32][33][34] . In our study, the rst two most common adverse effects reported were gastrointestinal disorders and skeletal muscle pain.…”
Section: Discussionmentioning
confidence: 99%